The Performance of Extension Workers Toward the Success of Rural Aquaculture Development Program in the East Sumba Regency,East Nusa Tenggara - Retang, Elfis Umbu Katongu; Susrusa, Ketut Budi; Sudarma, I Made (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 4 No 1 (2016), 2016)
The success of the aquaculture farming group in the development of rural aquaculture is highly determined by the cooperation and the commitment of the entire farming group, technical team, and extension institutions, particularly government employee and contract fishery assisting extension workers. The present study aimed to analyze the effects of extension workers’ performance and direct community assistance on the success of the Rural Aquaculture Development Program (Pengembangan Usaha Mina Perdesaan Perikanan Budidaya – PUMP-PB) in the East Sumba Regency. Data was analyzed using a descriptive qualitative and partial least square (PLS) method. Data collection was carried out by interview, observation, and documentation. Meanwhile, a census sampling method was employed to select a total of 102 respondents from 17 groups, from which 6 persons were selected (3 persons in management and 3 persons as members).  Results show that: 1) extension workers’ performance have a highly significant influence on the success of the Rural Aquaculture Development Program in the East Sumba Regency, with facilitating the strengthening of Pokdakan agencies as a dominant extension workers performance indicator; 2) the direct community assistance from the Rural Venture Development of Aquaculture have a significant impact on the success of Rural Aquaculture Development Program in the East Sumba Regency, with distribution of direct community assistance as a dominant extension workers performance indicator; 3) collectively, both the extension workers’ performance and the direct community assistance of PUMP-PB variables appears to have a significant influence on the success of the PUMP-PB program, with a coefficient of determination (R2) value of 27.90%.  The study suggests that it is imperative to increase the performance of extension workers in rural aquaculture development program in the East Sumba Regency, as it has been proven to have a positive impact on the success of the program. It is also necessary to extend the provision of direct community assistance, which has played a significant role in the success of the rural aquaculture development program. Further research is needed to determine other factors that may influence the success of the rural aquaculture development program in the East Sumba Regency.
Keywords: performance, extension workers, success of the Rural Aquaculture development program